The Role of Immersive Technologies in Improving Professional-Methodical Training of Biology Teachers - Raxmatova Salima Togaymuradovna (Zien Journals, 2024)
The article describes the digitalization of the system of continuous professional development of public education workers, the introduction of effective digital technologies online and offline for organizing the activities of national centers for training teachers in new methods, the consistent development of professional and methodological training of teachers, competency-based qualities and creative abilities. The possibilities, components, principles in the system of professional development and retraining of teachersbiologists, the improvement of their professional and methodological training in the digital environment, have been clarified
Keywords: Digital; professional; advanced training; digital knowledge